Flame retardancy performance and mechanism of polyvinyl alcohol films grafted amino acid ionic liquids with high transparency and excellent flexibility. (November 2022) - Liu, Meng; Cheng, Guojun; Tang, Zhongfeng; Zhou, Longxuan; Wan, Xianglong; Ding, Guoxin
Highlights: Flame retardant of PL films with good transparency were firstly designed and prepared. The flame retardant of PL films was improved and the PL films with UL94 V0 rating. Homogeneous dispersion of PL films can be achieved relying chemical-bands. Environmental-friendly PL films were prepared using a simple and low-cost method. Abstract: High transparency performance of polyvinyl alcohol (PVA) films with excellent flexibility plays an important role in wearable devices, solar cells displays and other fields. However, maintaining good transparency is a great challenge to prepare the flame retardancy PVA films. The PVA/L-Aspartic acid phosphate ionic liquid (AAILs) films (PL) with good transparency were firstly designed and prepared relying chemical-bands through sol-gel method. The flame retardancy and transparency performance of PL films were systematically characterized using various methods. The addition of AAILs did not affect the transparency of the PVA films, and the PL films had visible toughness and flexibility. Compared with the PVA films, the transparency and flame retardant performance of PL films were improved and the PL films with UL94 V0 rating and LOI of 30.1% were achieved when AAILs were added to 20.0 wt%. The homogeneous dispersion and high compatibility of AAILs in PVA films can be achieved relying chemical-bands using sol-gel method. The PL films had the high flame retardany performance and excellent flexiblility after the introduction of AAILs, while maintaining the transparency, biocompatibility and biodegradability. It provides a simple and low-cost method for the preparation of environmental-friendly flame retardant PL films.